Association of CNR1 gene and cannabinoid 1 receptor protein in the human brain. Issue 3 (28th November 2022) - Pak, Kyoungjune; Kantonen, Tatu; Pekkarinen, Laura; Nuutila, Pirjo; Nummenmaa, Lauri
Abstract: We aimed to integrate genomic mapping from brain mRNA atlas with the protein expression from positron emission tomography (PET) scans of type 1 cannabinoid (CB1) receptor and to compare the predictive power of CB1 receptor with those of other neuroreceptor/transporters using a meta‐analysis. Volume of distribution ( V T ) from F18‐FMPEP‐d2 PET scans, CNR1 gene (Cannabinoid receptor 1) expression, and H3‐CP55940 binding were calculated and correlation analysis was performed. Between V T of F18‐FMPEP‐d2 PET scans and CNR1 mRNA expression, moderate strength of correlation was observed ( rho = .5067, p = .0337). Strong positive correlation was also found between CNR1 mRNA expression and H3‐CP55940 binding ( r = .6336, p = .0364), validating the finding between F18‐FMPEP‐d2 PET scans and CNR1 mRNA. The correlation between V T of F18‐FMPEP‐d2 PET scans and H3‐CP55940 binding was marginally significant ( r = .5025, p = .0563). From the meta‐analysis, the correlation coefficient between mRNA expression and protein expressions ranged from −.10 to .99, with a pooled effect of .76. In conclusion, we observed the moderate to strong associations between gene and protein expression for CB1 receptor in the human brain, which was validated by autoradiography. We combined the autoradiographic finding with PET of CB1 receptor, producing the density atlas map of CB1 receptor. From the meta‐analysis, the moderate to strong correlation was observed between mRNA expression and protein expressions across multiple genes. Further study is needed to investigate the relationship between multiple genes and in vivo proteins to improve and accelerate drug development. Abstract : The moderate to strong associations between gene and protein expression for CB1 receptor in the human brain were observed and we produced the density atlas map of CB1 receptor for the first time in the human brain.